Evaluating the changes in economic and social development of Lithuanian counties by multiple criteria methods - Ginevičius, Romualdas; Podvezko, Valentinas (Technological and Economic Development of Economy, 2009)
Under the conditions of the country's economy restructurization, the differences between economic and social development of various regions are becoming more prominent. To smooth these differences, a number of scientific and practical problems associated with the concepts of a region, regional policy and its aims, determination of the boundaries of a region and evaluation of its development, etc., should be thoroughly investigated. To solve such complicated problems, multicriteria evaluation methods have been recently used, which could take into consideration the major aspects of economic and social development of the regions, including the environmental problems, as well as multidimensional character of the criteria, different directions of their changing and significances. Quantitative evaluation of social and economic region's development allows us to determine the changes, taking place in this development. This, in turn, shows the effectiveness of the EU structural funds, national programmes and other facilities used in conducting the regional policy.Lietuvos regionų (apskričių) ekonominės ir socialinės raidos pokyčiaiSantrauka. Šalies ūkiui iš esmės restruktūrizuojantis ir persitvarkant padidėja ekonominės ir socialinės plėtrosskirtumai tarp regionų (apskričių). Juos mažinant susiduriama su daugeliu mokslui ir praktikai aktualių, spręstinų klausimų, tokių kaip regiono, regioninės politikos samprata ir tikslai, jų ribų nustatymas, plėtros supratimas, įvertinimas ir t. t. Tokiems uždaviniams spręsti pastaraisiais metais sėkmingai taikomi daugiakriterinio vertinimo būdai. Jie leidžia įvertinti visus svarbiausius regionų ekonominės ir socialinės plėtros (RESP) aspektus, taip pat ir aplinkosauginius, įvertinti rodiklių daugiadimensiškumą, nevienodą kitimo kryptį bei reikšmingumą. Galimybė kiekybiškai įvertinti RESP leidžia nustatyti šios plėtros kaitą. Būtent ji parodo, koks yra Europos struktūrinių fondų, nacionalinių programų, kitų priemonių, skirtų regioninei politikai įgyvendinti, efektyvumas.Reikšminiai žodžiai: regionų plėtra, plėtros kriterijai, daugiakriteris vertinimas.First published online: 21 Oct 2010